Crystallization behavior and physical property of poly(ε‐caprolactone) tailored by a biocompatible linear diamide nucleating agent. Issue 5 (29th July 2019) - Tang, Jingjing; Li, Lingling; Wang, Xiaomin; Yang, Jinjun; Yue, Junjie; Yin, Jing; Qi, Zhicheng; Zhu, Zhen
Abstract: An organic diamide nucleating agent [EBH, N, N'−ethylenebis (12 − hydroxystearamide)] with eco‐friendliness was incorporated into the poly( ε ‐caprolactone) (PCL) to prepare a biocomposite. The differential scanning calorimetry results indicated that the crystallization temperature, crystallization rate and degree of crystallinity increased, and the crystallization time shortened for the PCL upon incorporation of the EBH. The crystal size decreased and crystal density increased with addition of the EBH. These evidences all showed that the EBH is an effective nucleating agent. Thermal stability of the PCL was enhanced substantially and mechanical property of the PCL was also improved. Mechanisms on enhanced thermal stability and improved mechanical property of the PCL tailored by the EBH were proposed and discussed. Abstract : The incorporated biocompatible EBH nucleating agent (NA) not only increased the crystallization temperature and crystallization rate and improved the mechanical property of the poly(ε‐caprolactone) (PCL), but also enhanced the thermal degradation temperature of the PCL. It can likely be attributed to good interfacial adhesion between the PCL and EBH, and the excellent flame retardant effect of the EBH on the PCL.